КАЗНЕНАТА ПОЛИТИКА НА СУДОВИТЕ ВО РЕПУБЛИКА МАКЕДОНИЈА ВО ПЕРИОДОТ 2007-2011 - Gruevska Drakulevski, Aleksandra (MACEDONIAN JOURNAL FOR CRIMINAL LAW AND CRIMINOLOGY, 2012)
This paper analysis the judicial penal policy in the Republic of Macedonia in the period 2007-2011, and not the legal penal policy or criminal sanctions by type and height prescribed by the law. In order to carry out consistent conclusions, first, the paper analyzes some important phenomenological features of the crime in the Republic of Macedonia in the analyzed period, in particular the scope of criminality and its structure according to the types of the committed criminal acts. Then, the paper analyzes the sanctions that are imposed by the type and height, than according to the types of criminal acts and according to the courts that had imposed them. For the purpose of the analysis of the penal policy in the Republic of Macedonia, official statistical data of the State Statistical Office of the Republic of Macedonia in the period from 2007 to 2011 are used. This research is particularly important because the analysis of the court's criminal policy is important to evaluate the effectiveness of various sanctions. The relationship between the case law of punishment and crime rates can be significant to extrapolate the effectiveness of various sanctions and to demonstrate to what extent particular sanctions are applied.
CRIMINAL POLICY OF THE COURTS IN THE REPUBLIC OF MACEDONIA IN THE PERIOD 2007-2011